STANDAR PEMBIAYAAN PENDIDIKAN DASAR - Izlyn, Nazera; Nurrabani, Nurrabani; Ananda Fitri, Dea; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research investigates the financing standards of the Basic Education Unit, highlighting the critical need for adequate funding to support various educational activities. Whether it is ongoing programs, future initiatives or long-term planning, every education unit depends on financial resources to function effectively. Education-related costs, including capital, operational and personnel expenditures, are subject to certain guidelines and standards. The Basic Education Cost Standards Education Policy provides a framework for schools to responsibly manage their financial resources in accordance with these standards, ensuring the efficient allocation of funds to achieve educational objectives. By adhering to these technical guidelines, education units can establish sound financing policies that are aligned with their objectives and improve overall educational outcomes.